Disulfiram and cancer immunotherapy: Advanced nano-delivery systems and potential therapeutic strategies - Di Huang; Yinsha Yao; Yifei Lou; Longfa Kou; Qing Yao; Ruijie Chen (International Journal of Pharmaceutics: X)
The initial focus of the clinical application of disulfiram was its efficacy in treating alcoholism. However, recent research has revealed its potential as an anti-tumor agent and even as an enhancer of cancer immunotherapy. Disulfiram has received safety approval from the FDA, indicating its safety advantages over other substances used for disease treatment. Although clinical trials have been conducted on strategies involving disulfiram or its combination with other anti-tumor drugs, the treatment outcomes have not yielded satisfactory results, thereby emphasizing the significance of addressing drug delivery as a crucial challenge to be resolved. The need to explore advanced nano-delivery systems and the potential immunotherapy enhancement effect of disulfiram in cancer treatment has increased. This review highlights various ways in which disulfiram can combat cancer and importantly, activate immune-related mechanisms. It also discusses obstacles related to delivering disulfiram and provides existing solutions in terms of drug delivery. These drug delivery strategies offer solutions to address various challenges encountered in diverse delivery methods and aim to achieve enhanced therapeutic effects. The focus is on recent advancements in disulfiram delivery strategies and the future potential of disulfiram in immune regulation.